2004
DOI: 10.1051/0004-6361:20031685
|View full text |Cite
|
Sign up to set email alerts
|

Fe II lifetimes and transition probabilities

Abstract: Abstract. Fe II radiative lifetimes were measured applying the time-resolved nonlinear laser-induced fluoresence technique. We investigated 21 levels of up to 47 000 cm −1 . The uncertainties are typically 2−3%. The lifetimes provide an improved absolute scale to our branching fractions which were measured with a Fourier transform spectrometer and a high-resolution grating spectrometer and which have been published earlier. We report absolute transition probabilities of 140 Fe II lines in the wavelength range … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 16 publications
1
37
2
Order By: Relevance
“…Fe  oscillator strengths increased in accuracy over the past 20 years as progressively more accurate TRLIF lifetimes were measured by Hannaford et al (1992), Schnabel et al (1999) and Schnabel et al (2004), and used to normalise earlier FTS and grating spectrometer emission BFs from Heise & Kock (1990) and Kroll & Kock (1987). Probably the most accurate g f -values now come from the compilation of , who used these and other experimental lifetimes to recalibrate and average a raft of theoretical and experimental BFs; we adopt these data for all our Fe  lines.…”
Section: Oscillator Strengthsmentioning
confidence: 91%
“…Fe  oscillator strengths increased in accuracy over the past 20 years as progressively more accurate TRLIF lifetimes were measured by Hannaford et al (1992), Schnabel et al (1999) and Schnabel et al (2004), and used to normalise earlier FTS and grating spectrometer emission BFs from Heise & Kock (1990) and Kroll & Kock (1987). Probably the most accurate g f -values now come from the compilation of , who used these and other experimental lifetimes to recalibrate and average a raft of theoretical and experimental BFs; we adopt these data for all our Fe  lines.…”
Section: Oscillator Strengthsmentioning
confidence: 91%
“…Unfortunately, these groups did not provide data for some Fe i lines that are important for the stellar iron spectrum analysis. Five sets of oscillator strengths from Meléndez & Barbuy (2009);Moity (1983); Raassen & Uylings (1998);Schnabel et al (2004), and the vald database (Kupka et al 1999) were inspected for Fe ii. We found that the solar mean abundance derived from the Fe ii lines varies between log ε = 7.41 ± 0.11 and log ε = 7.56 ± 0.05 depending on the source of g f -values (Table 1).…”
Section: Line Selection and Atomic Datamentioning
confidence: 99%
“…Those data were calibrated with the following experimental data: lifetimes of upper levels from Schnabel et al (2004), Schnabel et al (1999), Schnabel & Kock (2001), Guo et al (1992), Hannaford et al (1992), and Biémont et al (1991), and branching fractions by , Pauls et al (1990), and Kroll & Kock (1987). The (absorption) oscillator strength f lu is related to the branching fraction (BF lu ) and the lifetime (τ u ) by (e.g.…”
Section: Improved Oscillator Strengthsmentioning
confidence: 99%
“…The g f -values given by Schnabel et al (2004) for lines used in the solar iron abundance determination are very similar to those given in Schnabel et al (1999), and indeed the result given by Schnabel et al (2004) is the same (both in the mean value and line-to-line scatter) as in Schnabel et al (1999), A Fe = 7.42 (σ = 0.09); therefore, the revised values given by Schnabel et al (2004) do not improve the precision of their older transition probabilities. The g f -values given in the critical compilation of Fuhr & Wiese (2006) in the optical region are mainly based on the laboratory results of Schnabel et al (2004), which are not very precise as discussed above, and the (uncorrected) theoretical results of Raassen & Uylings (1998), which are not very accurate.…”
Section: The Solar Iron Abundancementioning
confidence: 99%